Application of empowerment education in health education for cancer patients - Yan Peng; Lin Han; Fang-Fang An; Li Li; Yue-Li Hou (Wolters Kluwer Medknow Publications, 2021)
Empowerment education aims to stimulate the intrinsic motivation of patients and make them pay more attention to their own health so as to control the disease. This paper expounds the concept, theoretical framework, implementer, object, implementation steps, forms, and evaluation methods of empowerment education for cancer patients, in order to provide practical guidance for clinical workers.